When Quranic Learning Goes Online: The Phenomenon of Yusuf Mansur in Da'wah Marketing Facing the Covid-19 Pandemic - Acep Aripudin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2023)
The Covid-19 (Corona viruses) pandemic has forced the system for spreading and understanding the Qur'an to be carried out online. Online media, such as e-learning, was known before the corona viruses season. One of the institutions implementing e-learning is the Darul Qur'an Islamic Boarding School, led by Yusuf Mansur. The famous preacher with the